Bases teórico-pedagógicas do atendimento educacional especializado das redes públicas municipais de educação de Aparecida de Goiânia/GO e Cascavel/PR - Santos, Ivone Rodrigues dos (2016)
This study aimed to analyze the administrative and pedagogical implications of theoretical and pedagogical basis that guide the Special Education and Inclusive Education policy,mainly to the supply and structuring of Specialized Educational Assistance (ESA) in municipal education networks of Aparecida de Goiânia / GO and Cascavel / PR.The research is characterized as a bibliographic and documentary research and field research, having as a procedure for data collection and registration, semi-structured interviews, recorded in audio. The analysis of data obtained through the legal regulations of the operationalization of the Specialized Educational Assistance (National Special Education Policy on Inclusive Education Perspective 2008, Resolution No. 4 of 02 October 2009, Decree No. 7611 of November 17, 2011); of current National Education Plan - PNE (BRAZIL, 2014); the guiding documents at the municipal level and the interviews were subsidized by theoretical and philosophical assumptions of Historical – critical Pedagogy, and Historical – Cultural Psychology. Based on a set of theoretical basis, here identified as "pragmatic miscellaneous" and "critical miscellaneous " we found that the municipalities are articulating differently the operation of this service. On the one hand , the ESA is being interpreted as a strategy to offset deficiencies of different orders , defending the organization of the pedagogical work centered on a productivist conception of education , limited to a man structuring naturalizing framework and considering the human being in the abstract, disconnected from a contextual engagement.On the other hand, following the same legal and operational guidelines, we find different possibilities to direct human development, without, however, losing sight of its educational specificity: the transmission of objective knowledge historically produced and interpreted as a condition for development. Based on the results, we emphasize the importance of educational theory guiding the educational practice, noting that overcoming the fragmented practices , fetishized and alienated , are the global social practice and / or educational practice is necessarily tied to a theory of critical praxis, transforming power relations, therefore, the historical, political and economic determinants affect the process